Enhanced absorption and cavity effects of three-photon pumped ZnO nanowires - Hollinger, Richard; Samsonova, Zhanna; Gupta, Dishiti; Spielmann, Christian; Roeder, Robert; Trefflich, Lukas; Ronning, Carsten; Kartashov, Daniil (Applied Physics Letters, 2017)
Semiconductor nanowire (NW) lasers attract a lot of attention as potential elements of nanophotonic circuits and lab-on-a chip devices. Here, we report on the experimental investigation of stimulated near ultraviolet (NUV) emission, pumped by three-photon absorption from near infrared femtosecond laser pulses, from ZnO NW arrays of different morphologies and compare it to the bulk. The spectrally and temporally resolved measurements of the NUV emission show both strong enhancements in the absorption and emission properties of the nanowire arrays compared to bulk samples. Thus, we determine a many times higher three-photon absorption in the nanostructure morphology compared to the bulk material. Furthermore, the threshold pumping intensity for stimulated emission in a vertically oriented nanowire array is twice lower and the emission onset time is shorter than in randomly oriented arrays, revealing strong influence of the macroscopic nanowire arrangement.
CRIS-Team Scopus Importer:2023-04-20